The complete guide to the national park lodges - Scott, David Logan, 1942-; Scott, Kay Woelfel (Globe Pequot, 2018)
Guide to U.S. national park lodges and accomodations. Includes maps, detailed information on rooms, rates, activities, food, and little known historical facts about the lodges.